2006
DOI: 10.1213/01.ane.0000217199.90426.7d
|View full text |Cite
|
Sign up to set email alerts
|

Chirality in Anesthesia I: Minimum Alveolar Concentration of Secondary Alcohol Enantiomers

Abstract: Most studies of chirality in inhaled anesthetic action have used the enantiomers of isoflurane. These enantiomers are expensive and scarce, which limits studies, such as the preliminary identification of molecular targets of anesthetic action, that can be performed with these isomers. We hypothesized that secondary alcohols (i.e., compounds having a -CH2-CHOH-CH3 group) that are experimental anesthetics would show enantioselectivity. To test this hypothesis, we determined the minimum alveolar anesthetic concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…S2 and Chiral Contribution to Phase Separation). Furthermore, different enantiomers of the same anesthetic molecule have been shown to have different potencies (70)(71)(72). Our theory presents a paradigm through which chirality affects physical membrane properties, in accordance with the classic hypothesis that anesthetic molecules disrupt membrane phase behavior (73,74).…”
Section: Discussionsupporting
confidence: 80%
“…S2 and Chiral Contribution to Phase Separation). Furthermore, different enantiomers of the same anesthetic molecule have been shown to have different potencies (70)(71)(72). Our theory presents a paradigm through which chirality affects physical membrane properties, in accordance with the classic hypothesis that anesthetic molecules disrupt membrane phase behavior (73,74).…”
Section: Discussionsupporting
confidence: 80%
“…Racemic alcohols were prepared from equal parts of each stereoisomer. The applied alcohol concentrations (16 mM 2-butanol; 4 mM 2-pentanol; and 2 mM 2-hexanol) are close to the blood alcohol concentrations measured at MAC in rats (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Alcohol vapor concentrations in equilibrium with perfusate were determined at the end of each experiment using headspace gas chromatography with a Carbowax column (Series 580; Gow-Mac, Bethlehem, PA), from which solution concentrations were calculated using previously determined Ostwald saline-gas partition coefficients at room temperature (11).…”
Section: Methodssupporting
confidence: 69%
“…In a companion paper (2) to the present essay, we report that two experimental volatile anesthetics that are readily available, 2-butanol and 2-pentanol, are enantioselective with respect to the minimum alveolar concentration preventing movement in 50% of individuals (MAC) in rats. The differences in MAC for these compounds are similar to those reported for isoflurane, with a 17% change in MAC for the 2-butanol isomers and a 38% change in MAC for the 2-pentanol isomers, compared with a MAC difference reported as 17% in one study (3) and 53% in another study (4) for the isomers of isoflurane.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…[62] developed a series of secondary alcohols, from 2-butanol till 2-heptanol from commercially available secondary alcohols, and tested their enantioselectivity by recording the minimum alveolar anaesthetic concentration (MAC) for these compounds. They found that the 2-butanol and 2-pentanol isomers were enantioselective, the S isomers having 17–38% higher MAC values than the R isomers.…”
Section: Basic Conceptsmentioning
confidence: 99%